Effects of Zika infection on growth - Arnaldo Prata‐Barbosa; Marlos Melo Martins; Andreia Bittencourt Guastavino; Antônio José Ledo Alves da Cunha (Brazilian Society of Pediatrics, 2019)
Objectives: To present the currently available evidence of the effects of congenital Zika virus infection on infant growth, to discuss possible intervening factors, and to describe preliminary data on this growth in a cohort of exposed children. Source of data: Non‐systematic review in PubMed, BVS, CAPES, Scopus, Web of Science, Cochrane and Google Scholar databases in the last 5 years, using the terms infection/disease by Zika virus and growth/nutrition/nutritional status/infant nutrition and nutritional needs. Additionally, the anthropometric data of the first 2.5 years of a cohort of children exposed to the Zika virus during pregnancy were reviewed. Synthesis of data: Both intrauterine growth restriction and low birth weight were reported in series of cases of children with congenital Zika syndrome. The postnatal growth deficit of these children appears to be directly proportional to the degree of neurological impairment. The etiology is multifactorial, and nutritional and non‐nutritional factors are probably involved. The data from the present cohort show that the head circumference evolution depends on this measurement at birth and that weight‐height growth has a trend toward lower weight and length in children with congenital microcephaly and normocephalic at birth who develop some neurological abnormality. Conclusions: The few existing data suggest that, in children with congenital Zika, the greater the degree of neurological impairment, the greater the impact on growth, whether or not associated with microcephaly at birth. Resumo: Objetivos: Apresentar as evidências atualmente disponíveis das repercussões da infecção congênita pelo vírus Zika no crescimento infantil, discutir possíveis fatores intervenientes e descrever dados preliminares desse crescimento em uma coorte de crianças expostas. Fonte dos dados: Revisão não sistemática nos portais de banco de dados PubMed, BVS, Capes, Scopus, Web of Science, Cochrane e Google Scholar nos últimos cinco anos, com o uso dos termos infecção/doença pelo vírus Zika e crescimento/nutrição/status nutricional/nutrição infantil e necessidades nutricionais. Além disso, foram revistos os dados antropométricos dos primeiros dois anos e meio de uma coorte de crianças expostas ao vírus Zika durante a gestação. Síntese dos dados: Tanto a restrição do crescimento intrauterino como o baixo peso ao nascer têm sido relatados em séries de casos de crianças com síndrome de Zika congênita. O déficit de crescimento pós‐natal dessas crianças parece ser diretamente proporcional ao grau de comprometimento neurológico. A etiologia é multifatorial, com fatores nutricionais e não nutricionais provavelmente envolvidos. Os dados de nossa coorte mostram que a evolução do perímetro cefálico é dependente do valor dessa medida ao nascimento e que o crescimento pondero‐estatural apresenta uma tendência de menor peso e comprimento em crianças com microcefalia congênita e normocefálicas ao nascimento, mas com alguma anormalidade neurológica evolutiva. Conclusões: Os poucos dados existentes sugerem que em crianças com Zika congênita, o impacto sobre o crescimento será tanto maior quanto maior for o grau de comprometimento neurológico, associado ou não à microcefalia ao nascimento. Keywords: Zika virus infection, Growth, Microcephaly, Palavras‐chave: Infecção pelo Zika vírus, Crescimento, Microcefalia